Pengaruh Tingkat Diskonto dan Analisis Sensitivitas terhadap Keputusan Capital Budgeting pada Proyek Investasi Jangka Panjang - Khatimah, Khusnul; Muchran, Muchriana (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
This study explores the impact of discount rate determination and sensitivity analysis on capital budgeting decisions for long-term investment projects. Amid rising economic uncertainty and risk volatility, the selection of an appropriate discount rate such as through the Weighted Average Cost of Capital (WACC) or the Capital Asset Pricing Model (CAPM) is critical in accurately assessing project feasibility. The study aims to evaluate how minor changes in discount rates can significantly affect Net Present Value (NPV) calculations and how sensitivity analysis can serve as a tool for risk mitigation. Using a qualitative approach based on literature review, this research synthesizes theoretical and empirical studies published between 2021 and 2025. The findings indicate that discount rate selection plays a decisive role in capital budgeting, especially for projects with complex cash flows. Sensitivity analysis, including one-way, two-way, and scenario analysis, enhances decision-making by identifying key risk variables. The study also highlights challenges in Indonesian corporate practices, such as limited analytical capacity and the lack of standard risk-based discounting methods. An integrative framework is proposed, consisting of strategic alignment assessment, multi-criteria discount rate formulation, comprehensive sensitivity analysis, and continuous monitoring. The research contributes to financial decision-making literature and offers practical guidance for more robust and adaptive investment evaluation, especially in emerging markets.